Mid‐Pleistocene thin‐skinned glaciotectonic thrusting of the Aberdeen Ground Formation, Central Graben region, central North Sea. (26th January 2016) - Vaughan‐Hirsch, David P.; Phillips, Emrys R.
ABSTRACT: This paper presents the results of a high‐resolution 2D seismic survey of mid‐Pleistocene glaciogenic sediments in the Central Graben region of the central North Sea. Sediments have undergone major glaciotectonic thrusting and folding associated with the repeated southerly advance of a mid‐Pleistocene ice sheet. The total observed length of the thrust‐stacked section is approximately 5–6 km, comprising a series of discrete thrust slices, which range in length from < 300 m to > 700 m. The basal detachment of the thrust complex occurs at a depth of ca. 220 m below the sea bed within the upper Aberdeen Ground Formation. A thin‐skinned glaciotectonic model involving proglacial to ice‐marginal glaciotectonic thrusting followed by post‐tectonic deposition is proposed. Initial ice advance led to the over‐pressurizing of groundwater within a laterally extensive sand sheet in the upper Aberdeen Ground Formation, promoting the formation of a major décollement surface at the base of the developing thrust‐stack. Over‐pressurization of the groundwater system is thought to have occurred in response to rapid ice advance, suggesting that the development of large‐scale thrust complexes may be associated with surge‐type behaviour. The proposed model evidences complex dynamics of mid‐Pleistocene ice sheets within the central North Sea.